Retrospective database analysis of healthcare resource utilization and costs in patients who develop post-transplant lymphoproliferative disease within the first year following allogeneic hematopoietic stem cell transplants. (2nd October 2020) - Watson, Crystal; Xu, Hairong; Princic, Nicole; Sruti, Ila; Barlev, Arie
Abstract: Aims: Healthcare resource utilization (HRU) and costs in post-transplant lymphoproliferative disease (PTLD) patients following allogeneic hematopoietic stem cell transplant (HCT) were evaluated in the USA. Methods: MarketScan Commercial and Medicare Supplemental database claims from 01 July 2010 to 31 December 2017 were analyzed. Patients eligible for analysis received allogeneic HCT between 01 January 2011 to 31 December 2015, had ≥6 months of continuous enrollment before HCT, and had ≥1 claim for PTLD or ≥1 inpatient or ≥2 outpatient claims for a clinically-relevant lymphoma within 1 year following HCT (PTLD index = first claim of diagnosis). Patients with clinically-relevant lymphomas within 6 months before HCT were excluded. HRU and total paid amounts were assessed from the week before the HCT through 1-day pre-PTLD index (HCT to PTLD) and monthly from PTLD index through 1-year post-PTLD index. HRU is reported as mean (SD). Results were also provided by survival status. Results: Overall, 92 patients were eligible for analysis. From HCT to PTLD, 98.9% of patients were hospitalized, with 1.7 (1.2) hospitalizations/patient. The average length of stay was 25.3 (22.2) days/patient. From HCT to PTLD, 98.9% of patients had outpatient services with 233.7 (261.1) services/patient and 91.3% of patients had a prescription fill with 32.9 (26.0) prescriptions/patient. In the first month post-PTLD index, 51.2% of patients were hospitalized. Mean paid amounts were $399, 470/patient (range $7542–$1.7 M) from HCT to PTLD. Cumulative mean paid amounts 1-year post-PTLD were $429, 043/patient. Total cost/patient/month was ∼7 times higher in patients who died ( n  = 49; $232, 591) than those who lived ( n  = 43; $33, 677). Costs were mainly driven by hospitalizations. Limitations: Limitations include those inherent to retrospective analyses (i.e. miscoding, lack of clinical detail). Conclusions: HRU and costs from HCT to PTLD were high and more than doubled within 1-year post-PTLD. PTLD patients who died had ∼7 times higher costs than those who lived, driven by hospitalizations. Effective treatments are needed to reduce the burden of PTLD.